Alyawarra : an Aboriginal language of central Australia - Yallop, Colin; Australian Institute of Aboriginal Studies (Canberra : Australian Institute of Aboriginal Studies, 1977)
Description of the Alyawarra language and notes on Arandic forms and the Arandic languages; phonology; morphology syntax; Alyawarra-English glossary; English-Alyawarra word lists.
Bibliography: p. 166-167.
Keywords: Australian Aboriginal languages. Alyawarra language; Alyawarra language; Alyawarr / Alyawarre language (C14) (NT SF53-07); Language - Vocabulary - Word lists; Language - Linguistics - Grammar and syntax; Arandic language group; Language - Linguistics - Language classification; Alyawarr / Alyawarre people (C14) (NT SF53-07); Language - Linguistics - Phonology and phonetics; Northern Territory - Central NT